Analisis Keterampilan Mengajar Mahasiswa Pendidikan Fisika pada Program Pengenalan Lingkungan Persekolahan (PLP) - Sonia, Mita; Qaddafi, Muhammad; Jamilah, Jamilah (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This research is a quantitative descriptive study. The subjects in this study were Physics Education students, Class of 2021. The research instrument used was the Introduction to School Environment 2 (PLP 2) assessment instrument. Furthermore, the data analysis technique used in this study was quantitative descriptive analysis which included mean scores, diagrams, and categorization. The results of the study showed that the teaching skills of Physics Education students, Class of 2021 had met the criteria as good prospective educators, as seen from the preliminary stage, core stage, closing stage and the personality of prospective educator students in the learning process. This is evidenced by the average preliminary stage assessment obtained of 28.22 which is in the very good category, then the average core stage assessment of 165.86 which is in the very good category, and the average closing stage assessment of 36.19 which is in the very good category, and the average personality assessment of 167.91 which is in the very good category. Based on this, it can be concluded that the teaching skills of Physics Education students are in the very good category, and have met the criteria as good prospective educators.